Getting sharper: the brain under the spotlight of super-resolution microscopy - Arizono, Misa; Idziak, Agata; Quici, Federica; Nägerl, U. Valentin (Trends in cell biology, 2023)
Brain cells such as neurons and astrocytes exhibit an extremely elaborate morphology, and their functional specializations like synapses and glial processes often fall below the resolution limit of conventional light microscopy. This is a huge obstacle for neurobiologists because the nanoarchitecture critically shapes fundamental functions like synaptic transmission and Ca2+ signaling. Super-resolution microscopy can overcome this problem, offering the chance to visualize the structural and molecular organization of brain cells in a living and dynamic tissue context, unlike traditional methods like electron microscopy or atomic force microscopy. This review covers the basic principles of the main super‐resolution microscopy techniques in use today and explains how their specific strengths can illuminate the nanoscale mechanisms that govern brain physiology. Super-resolution microscopy (SRM) has a spatial resolution that surpasses the classic diffraction limit, providing access to cellular and molecular structures of the brain on a nanometric scale.Laser-scanning SRM techniques such as stimulated emission depletion (STED) lend themselves to imaging deep inside living brain tissue and even the intact brain in vivo, making it possible to study the links between microanatomy, neurophysiology, and animal behavior.Single-molecule localization microscopy can achieve a single-digit nanometer resolution – albeit only mostly in cell cultures for now. It has been used to reveal new facets of the neuronal cytoskeleton and the dynamic molecular organization of chemical synapses.Recently, new SRM approaches have been developed to visualize the extracellular space of the brain, opening up a new frontier in neuroscience, with potentially major implications for basic and clinical research.